Systems-thinking skills exhibited by UiTM Sarawak Diploma students in solving non-routine problems / Chin-Ying Liew ... [et al.] - Liew, Chin-Ying; Foo, Kien-Kheng; Lee, Elinda Ai-Lim; Goh, Kelvin Tee-Hiong (Research Management Institute (RMI), 2008)
It is hypothesized that systems thinking can play a leading role in facilitating the attainment of important problem-solving skills especially in the context of solving ill-defined problems involving uncertainties and dynamic complexities. As part of an initial effort to determine if there is any basis for saying so, this exploratory study seeks to investigate the systems-thinking skills that are exhibited by two hundred thirty-three UiTM Sarawak Diploma students in solving non-routine problems. Moreover, it also aims to investigate the influence of three demographic factors, that is, gender, Gugusan and Cumulative Grade Point Average (CGPA) on systems-thinking skills. A framework for categorizing systems-thinking skills was developed to measure these aforementioned skills as the respondents solved four non-routine problems. This study used the survey research design to gather data through apaper-and-pencil test and questionnaire. Four performance tasks were used to measure these skills. Following that, the performance of each respondent was calculated based on an analytical scoring rubric for the identified systems thinking skills. Both descriptive and inferential data analysis were carried out. Findings indicated that the respondents score poorly in systems-thinking performance. The mean score for systems thinking was found to be only 11.76 out of a possible 50. With regard to the three preselected demographic factors, it was found that systems-thinking skills show no dependency with respect to gender (t = .202, P > .05) but was found to be dependent upon Gugusan (F = 4.500, P<.05) andCGPA (F = 5.554, P < .05). The limitations of this study were also discussed. The findings have implications of great importance in the teaching of systems thinking to students. The study ended with some suggestions for future research.